Free Medial Meniscal Fragment Which Mimics the Dislocated Bucket-Handle Tear on MRI - Faik Türkmen; İsmail Hakkı Korucu; Cem Sever; Mehmet Demirayak; Gani Goncü; Serdar Toker (Case Reports in Orthopedics, 2014)
The bucket-handle meniscal tear is a specific type of meniscal injuries which has specific signs on MRI. An attached fragment displaced away from the meniscus with any type of tear causes bucket-handle tear of the meniscus. Magnetic resonance imaging (MRI) is the most commonly used diagnostic tool for meniscal injuries. We present a case of free medial meniscal fragment which mimics the dislocated bucket-handle tear on MRI. The presence of “fragment within the intercondylar notch sign” and “the absence of the bow tie sign” may be an indication of a free meniscal fragment. This should be considered during diagnosis.